2017
DOI: 10.1080/1828051x.2017.1373609
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dietary chitosan on growth performance, haematological parameters and gut function in broilers

Abstract: Percentages of antimicrobial resistance to Salmonella and Escherichia coli in poultry products were high in Thailand, thus, alternative to antibiotic growth promoter is required. The objective of this experiment aimed to examine the effect of dietary chitosan in broilers on blood and intestinal changes. Total of 392, day-old male Ross 308 broilers were allotted into four groups. Broilers in the control group (group 1) received commercial corn-soybean meal-based basal diet. Chicks in group 2 received basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…In this study, dietary CT and/or CS had no significant (P > 0.05) effect on the jejunal and duodenal VH of experimental chickens. This suggests that dietary CT and CS did not trigger programmed cell death, and this agreed with the findings of Nuengjamnong and Angkanaporn (2018) from a study in broiler chickens. This agreement may be due to the similarity in the physicochemical properties of CS used in both studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, dietary CT and/or CS had no significant (P > 0.05) effect on the jejunal and duodenal VH of experimental chickens. This suggests that dietary CT and CS did not trigger programmed cell death, and this agreed with the findings of Nuengjamnong and Angkanaporn (2018) from a study in broiler chickens. This agreement may be due to the similarity in the physicochemical properties of CS used in both studies.…”
Section: Discussionsupporting
confidence: 90%
“…Also, according to Meibom et al (2005) chitin or its derivatives was reported to influence the expression of 41 genes of Vibrio cholera. Dietary chitin (CT), a β-(1–4)-N- acetyl-d-glucosamine, and chitosan ( CS ), a β-(1–4)- linked d-glucosamine isolated from crustacean, are known to affect growth performance of broiler chickens (Kobayashi et al, 1996; Nuengjamnong and Angkanaporn, 2018), however, their mechanism of action is still a topic of concern. There is a gross dearth of information on the effect of dietary CT and CS on the gut morphology, mRNA expression of intestinal nutrient transporters and growth hormone (GH) in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the nano-chitosan-added diets had no effect on serum cholesterol and triglyceride of broilerscompared with the control group. The results obtained agree with those reported by Nuengjamnong and Angkanaporn (2017) who found that feeding the broiler chicks on chitosan-supplemented diet had no effect on serum cholesterol and triglyceride.…”
Section: Blood Parameterssupporting
confidence: 91%
“…The increment in fresh and dry biomass could be associated with the increment in plant growth and development. On the other hand, previous researchers had confirmed the growth enhancement of chitosan on several crops (Anusuya and Sathiyabama, 2016;Yan et al 2017;Nuengjamnong and Angkanaporn, 2018). Hence, increment in fresh and dry leaf yield could be a great contribution to the farmers.…”
Section: Fresh and Dry Weight Of Leafmentioning
confidence: 92%